Assessing the Acceptability and Feasibility of Five Cycles of Seasonal Malaria Chemoprevention in Côte d’Ivoire - Orphée Kangah; Issaka Zongo; Alassane Haro; William Yavo (Tropical Medicine and Infectious Disease)
Seasonal malaria chemoprevention (SMC) is a strategy recommended by the World Health Organization for children aged 3–59 months in the Sahel and sub-Sahel regions where malaria transmission is seasonal. In Côte d’Ivoire, malaria remains a high priority and accounts for the majority of consultations and deaths in children under five. The recent revision of the criteria for the introduction of seasonal malaria chemoprevention has made the north of Côte d’Ivoire, where malaria transmission is seasonal, eligible for the SMC. We conducted a pilot study in this part of the country to assess the acceptability and feasibility of five cycles of SMC in 1701 children. Seasonal malaria chemoprevention with sulfadoxine–pyrimethamine + amodiaquine (SP + AQ) was administered monthly to eligible children over five months. A qualitative approach and quantitative surveys were used to assess the strategy acceptability and feasibility in the study area. Overall, there was a positive perception, attitude, and adherence towards the seasonal malaria chemoprevention in this study area.